2017
DOI: 10.1016/j.dci.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation, evolution and expression analysis of g-type lysozymes in Ciona intestinalis

Abstract: a b s t r a c tLysozyme is an important defense molecule of the innate immune system. Known for its bactericidal properties, lysozyme catalyzes the hydrolysis of b-(1,4)-glycosidic bonds between the N-acetyl glucosamine and N-acetyl muramic acid in the peptidoglycan layer of bacterial cell walls. In this study, the complete coding sequence of four g-type lysozymes were identified in Ciona intestinalis. Phylogenetic analysis and modelling supported the hypothesis of a close relationship with the vertebrate g-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…chicken-type (c-Lyz) and goose-type (g-Lyz) (Callewaert & Michiels, 2010;Callewaert et al, 2012;Zhang et al, 2018). The c-and g-type of lysozymes have been demonstrated to play important roles in the immune defense in many fish species, especially in protection against pathogenic bacterial infection (Liu et al, 2016;Wang et al, 2016;Di Falco et al, 2017;Gou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…chicken-type (c-Lyz) and goose-type (g-Lyz) (Callewaert & Michiels, 2010;Callewaert et al, 2012;Zhang et al, 2018). The c-and g-type of lysozymes have been demonstrated to play important roles in the immune defense in many fish species, especially in protection against pathogenic bacterial infection (Liu et al, 2016;Wang et al, 2016;Di Falco et al, 2017;Gou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some kinds of C‐type lysozymes were also involved in shrimp antiviral response (Karthik et al, ; Mai & Wang, ). The lysozymes also had other functions, such as antitumour, anti‐inflammatory, digestion, immune‐enhancing and feed preservation (Di Falco, Cammarata, & Vizzini, ; Irwin, ; Lee, Ku, Na, & Bae, ). Indeed, the lysozymes may act as a multipurpose defence factor and play vital roles in the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Both lysozymes gene has been demonstrated to play essential roles as the immune defense in many fish species (Mohanty dan Sahoo 2010;Pridgeon et al 2013;Wei et al 2014;Di Falco et al 2017). The involvement of the LYSC in the protection against bacterial infection has been reported in fish species, such as resistant families of Atlantic salmon against Piscirickettsia salmonis infection (Dettleff et al 2015), channel catfish against Edwardsiella ictaluri (Wang et al 2013), Darby's sturgeon and Qihe crucian carp against A. hydrophila (Wang et al 2016;Zhang et al 2018), Moreover, the single nucleotide polymorphisms (SNPs) in LYSC gene have been characterized in several fish species, such as Asian seabass (Fu et al 2013) and Japanese flounder (Liu et al 2017) and identified as potential markers for bacterial-resistance in fish.…”
Section: Introductionmentioning
confidence: 99%